Pharmacometric dose optimization of buprenorphine in neonatal opioid withdrawal syndrome - Rena Eudy‐Byrne; Nicole Zane; Susan C. Adeniyi‐Jones; Marc R. Gastonguay; Ana Ruiz‐Garcia; Gagan Kaushal; Walter K. Kraft (Wiley, 2021)
Abstract Results from Blinded Buprenorphine OR Neonatal morphine solution (BBORN), a previous phase III trial in infants with neonatal opioid withdrawal syndrome (NOWS), demonstrated that sublingual buprenorphine resulted in a shorter duration of treatment and shorter length of hospital stay than the comparator, oral morphine. Objectives of Buprenorphine Pharmacometric Open Label Research study of Drug Exposure (BPHORE), a new trial with buprenorphine in a similar population, were to (1) optimize initial dose, up‐titration to achieve symptom control and weaning steps of pharmacologic treatment and (2) investigate safety of the revised regimen. A pharmacodynamic model linked buprenorphine exposure to NOWS symptom scores. Adaptive dose regimens were simulated using BBORN results to compare dosing regimens for times to stabilization, weaning, and cessation. A clinical trial using model informed doses (BPHORE), was conducted. Simulations indicated benefits in time to stabilization and weaning when up‐titration rates increased to 30%. Stabilization time was not greatly impacted by the starting dose. Time to wean and time to cessation were dose dependent. A weaning rate of 25% shortened time to cessation. Ten infants were enrolled in BPHORE using buprenorphine starting dose of 24 µg/kg/day, 33% titration, and 15% wean rate. Five subjects required adjuvant therapy. Half‐maximal effective concentration (EC50) values indicated maximum buprenorphine doses did not generate maximal effect size, suggesting potential efficacy of a further increased dose if a goal was to reduce the use of adjunct agents. Simulations indicated that further benefits can be gained by increasing starting doses of buprenorphine and increasing wean rates. Use of a model‐based analysis to provide focused guidelines for care can be used with goals of reducing treatment time and hospital stays in infants with NOWS.